A Bifunctional Electrocatalyst for Oxygen Evolution and Oxygen Reduction Reactions in Water. Issue 7 (15th January 2016) - Schöfberger, Wolfgang; Faschinger, Felix; Chattopadhyay, Samir; Bhakta, Snehadri; Mondal, Biswajit; Elemans, Johannes A. A. W.; Müllegger, Stefan; Tebi, Stefano; Koch, Reinhold; Klappenberger, Florian; Paszkiewicz, Mateusz; Barth, Johannes V.; et al.
Abstract: Oxygen reduction and water oxidation are two key processes in fuel cell applications. The oxidation of water to dioxygen is a 4 H + /4 e − process, while oxygen can be fully reduced to water by a 4 e − /4 H + process or partially reduced by fewer electrons to reactive oxygen species such as H2 O2 and O2 − . We demonstrate that a novel manganese corrole complex behaves as a bifunctional catalyst for both the electrocatalytic generation of dioxygen as well as the reduction of dioxygen in aqueous media. Furthermore, our combined kinetic, spectroscopic, and electrochemical study of manganese corroles adsorbed on different electrode materials (down to a submolecular level) reveals mechanistic details of the oxygen evolution and reduction processes. Abstract : Leading a double life : A manganese corrole complex has been shown to serve as a bifunctional catalyst for the electrocatalytic generation of dioxygen and reduction of dioxygen in aqueous solution. The complex oxidizes hydroxide ions to molecular oxygen through a four‐electron process in weak to moderate alkaline conditions and reduces O2 in a two‐electron process to hydrogen peroxide.